Search for light sterile neutrinos with the T2K far detector Super-Kamiokande at a baseline of 295 km - Abe,K; Akutsu,R; Ali,A; Andreopoulos,C; Anthony,L; Antonova,M; Aoki,S; Ariga,A; Ashida,Y; Awataguchi,Y; Azuma,Y; Ban,S; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2019)
We perform a search for light sterile neutrinos using the data from the T2K far detector at a baseline of 295 km, with an exposure of 14.7(7.6)×1020 protons on target in neutrino (antineutrino) mode. A selection of neutral-current interaction samples is also used to enhance the sensitivity to sterile mixing. No evidence of sterile neutrino mixing in the 3+1 model was found from a simultaneous fit to the charged-current muon, electron and neutral-current neutrino samples. We set the most stringent limit on the sterile oscillation amplitude sin2θ24 for the sterile neutrino mass splitting Δm241<3×10−3  eV2/c4.